Acute Colonic Pseudoobstruction - Chudzinski, Allen P.; Thompson, Earl V.; Ayscue, Jennifer M. (Clinics in Colon and Rectal Surgery, 2015)
Acute colonic pseudoobstruction (ACPO), often referred to as Ogilvie syndrome, is a clinical entity characterized by severe colonic distension (adult acute megacolon) in the absence of mechanical obstruction. It can result in abdominal ischemia and perforation if left untreated. This article discusses the epidemiology and current pathophysiologic theories of ACPO as well as the clinical presentation and diagnostic modalities utilized to identify the disease. In addition, this article describes the current treatment options for ACPO, which range from conservative medical therapy, therapeutic endoscopy, to subtotal colectomy.
Keywords: colonic ileus; acute colonic pseudoobstruction; Ogilvie syndrome; large bowel obstruction